Retinal Phenotype in the rd9 Mutant Mouse, a Model of X-Linked RP - Falasconi, Antonio; Biagioni, Martina; Novelli, Elena; Piano, Ilaria; Gargini, Claudia; Strettoi, Enrica (Frontiers in Neuroscience, 2019)
Retinal degeneration 9 (rd9) mice carry a mutation in the retina specific “Retinitis Pigmentosa GTPase Regulator (RPGR)” Open Reading Frame (ORF) 15 gene, located on the X chromosome and represent a rare model of X-linked Retinitis Pigmentosa (XLRP), a common and severe form of retinal degeneration (Tsang and Sharma, 2018; Wright et al., 2010). The rd9 RPGR-ORF15 mutation in mice causes lack of the protein in photoreceptors and a slow degeneration of these cells with consequent decrease in Outer Nuclear Layer (ONL) thickness and amplitude of ERG responses, as previously described (Thompson et al., 2012). However, relative rates of rod and cone photoreceptor loss, as well as secondary alterations occurring in neuronal and non-neuronal retinal cell types of rd9 mutants remain to be assessed. Aim of this study is to extend phenotype analysis of the rd9 mouse retina focusing on changes occurring in cells directly interacting with photoreceptors. To this purpose, first we estimated rod and cone survival and its degree of intraretinal variation over time; then, we studied the morphology of horizontal and bipolar cells and of the retinal pigment epithelium (RPE), extending our observations to glial cell reactivity. We found that in rd9 retinas rod (but not cone) death is the main cause of decrease in ONL thickness and that degeneration shows a high degree of intraretinal variation. Rod loss drives remodeling in the outer retina, with sprouting of second-order neurons of the rod-pathway and relative sparing of cone pathway elements. Remarkably, despite cone survival, functional defects can be clearly detected in ERG recordings in both scotopic and photopic conditions. Moderate levels of Muller cells and microglial reactivity are sided by striking attenuation of staining for RPE tight junctions, suggesting altered integrity of the outer Blood Retina Barrier (BRB). Because of many features resembling slowly progressing photoreceptor degeneration paradigms or early stages of more aggressive forms of RP, the rd9 mouse model can be considered a rare and useful tool to investigate retinal changes associated to a process of photoreceptor death sustained throughout life and to reveal disease biomarkers (e.g. BRB alterations) of human XLRP.